2016
DOI: 10.3402/fnr.v60.30876
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orally administeredBacillus coagulansand inulin on prevention and progression of rheumatoid arthritis in rats

Abstract: BackgroundProbiotics have been considered as an approach to addressing the consequences of different inflammatory disorders. The spore-forming probiotic strain Bacillus coagulans has demonstrated anti-inflammatory and immune-modulating effects in both animals and humans. The prebiotic inulin also potentially affects the immune system as a result of the change in the composition or fermentation profile of the gastrointestinal microbiota.ObjectiveIn the present study, an in vivo model was conducted to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 22 publications
2
48
0
4
Order By: Relevance
“…Some performed studies evaluating the effect of probiotics as an adjuvant therapy for RA treatment have shown no significant results . Some of these conducted studies have smaller numbers of patients and a short period of treatment .…”
Section: Probiotic Applications In Autoimmune Diseasesmentioning
confidence: 99%
“…Some performed studies evaluating the effect of probiotics as an adjuvant therapy for RA treatment have shown no significant results . Some of these conducted studies have smaller numbers of patients and a short period of treatment .…”
Section: Probiotic Applications In Autoimmune Diseasesmentioning
confidence: 99%
“…Notably, Bifidobacterium infantis 35624 induces IL‐10 and TGF‐β production in DCs isolated from human MLNs and increases the number of FOXP3 + T reg cells in human peripheral blood; B. bifidum LMG13195 enhances the expression of CCL20, CCL22, CXCL10, CXCL11, IL‐28, and IL‐29 in an epithelial intestinal cell line (HT29), which are able to drive the generation of CD4 + CD25 (high) T reg cells; L. crispatus KT‐11 enhances IgA secretion by IECs; and L. rhamnosus GG activates macrophages through TLR2 and induces IL‐10 production in vitro . In most cases, mixtures of probiotics have been used in animal models of diseases, and enhancement in IEC functions and modulation of immune system have been reported …”
Section: Microbiota and Probiotic Interactions In The Gutmentioning
confidence: 99%
“…administered Bacillus coagulans to a rheumatoid arthritis rat model before disease induction and observed an improvement of the clinical parameter, promoting a decrease in TNF‐α serum levels and serum amyloid A (SAA) . Since TNF‐α and SAA are able to recruit lymphocytes and mediate matrix degradation leading to joint damage, the downregulation of these molecules could counteract the inflammation . Several studies have reported contrasting results on the beneficial effects of administration of some probiotics to rheumatoid arthritis patients.…”
Section: Microbiota and Probiotics In Autoimmune Diseasesmentioning
confidence: 99%
“…In separate studies of humans and rats, oral intake of Bacillus coagulans (B. coagulans) improved the disease activity of RA. 26,27 Mandel et al 26 reported. There were statistically significant improvements in the treatment group.…”
Section: Bacillus Coagulansmentioning
confidence: 99%